Perlakuan Lama Simpan dan Macam Pembungkus Entres Mangga (Mangifera indica L.) terhadap Pertumbuhan Bibit Sambung Pucuk - Putri, Aura Nabita; Kusumaningrum, Nora Augustien; Nugrahani, Pangesti (Universitas Lampung, 2024)
Mango (Mangifera indica L.) can be developed through plant propagation by the method of shoot-tip grafting. The problem that often take place is the distance between the mother tree and the location of the connection that is far apart, so it takes a long time and is tough to finish within one day. This research aims to obtain a combination of shelf life and types of scion wrapping materials on the growth of mango seedlings. The research conducted in April - August 2023 at UPT Horticultural Seed Development using Complete Randomized Design (CRD) with 2 factors 3 replications. The first factor is storage time (L) (0 days, 2 days, 4 days, and 6 days) and the second factor is the type of wrapping materials (M) (without packaging, banana frond wrapping, newspaper wrapping, and coconut husk wrapping). Parameters include the time at which shoots appear, the percentage of viable grafting, the length of the shoots and the total number of leaves. The results showed that in general the percentage of success was 70%. The treatment of storage time and type of entres wrapper did not affect the percentage of live grafting, but at a storage time of 2 days, the fastest results were obtained at the time of bud emergence and the longest results in bud length. Keywords: Entry, Length of Storage, Type of Wrapping, Mango Shoot Grafting